2017
DOI: 10.3390/f8060214
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Accumulation and Decomposition from Coarse Woody Debris in a Naturally Regenerated Korean Red Pine (Pinus densiflora S. et Z.) Forest

Abstract: Abstract:The contribution of coarse woody debris (CWD) to forest carbon (C) and nitrogen (N) dynamics is poorly quantified. This study quantified total C and N content in CWD and estimated the decomposition rates of CWD at different decay stages in a 70-year-old naturally regenerated Korean red pine forest (Pinus densiflora S. et Z.). The N concentration in CWD varied among species and decay classes (from 0.15% to 0.82%), and exhibited a decreasing pattern in C:N ratios with increasing decay class. Total CWD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…This relative N limitation might enhance soil microbial affinity for N uptake as well as N immobilization into pine CWD [2]. However, soil microbes beneath CWD might be unable to fully utilize additional C sources in the short term because soil N availability could act as a limiting factor for microbial growth under the N limited condition by CWD [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This relative N limitation might enhance soil microbial affinity for N uptake as well as N immobilization into pine CWD [2]. However, soil microbes beneath CWD might be unable to fully utilize additional C sources in the short term because soil N availability could act as a limiting factor for microbial growth under the N limited condition by CWD [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that CWD decomposition was generally faster in the southern forests than in the central forests, which might be due to higher temperature and increased arthropod activity in southern Korea [31]. Fast CWD decomposition due to these factors might accelerate substrate emission from CWD and thus promote microbial N immobilization to CWD and soils [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few studies on litter decomposition have been conducted in pine forests, there is limited information on the effects of physicochemical litter quality on decomposition of different pine litter species, because these studies contain only a simple description of changes in nutrient elements in decaying litter [38][39][40][41]. Moreover, it is difficult to directly compare the results of these studies, because each pine species was independently studied at different times, with varying areas, litter type, and forest floor characteristics [38][39][40][41][42][43][44][45][46]. Also, it is not clear if the differences in decomposition rate of each type of pine litter is attributable to the kinds of environmental conditions present or the chemical properties of the litter.…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus maculata 0.049 New Zealand (Ganjegunte et al 2004) (43°S,172°E) Pinus radiata 0.074 Chronosequence (13 a) Greater Khingan Mountains (Xu 1988 as C c and N c are related to species, and there are great differences between species. Nitrogen content in CWD varied between species and decay classes (0.15%-0.82%), and C/N ratios showed a decreasing trend with increasing decay class (Noh et al 2017). For six common species of deciduous temperate forests over 40 months, mass loss was negatively correlated with initial lignin concentration and positively correlated with initial cellulose concentration and density (Cha et al 2017).…”
Section: Decomposition Processmentioning
confidence: 99%